Current and Past Infections of HBV Do Not Increase Mortality in Patients With COVID‐19 - Yip, Terry Cheuk‐Fung; Wong, Vincent Wai‐Sun; Lui, Grace Chung‐Yan; Chow, Viola Chi‐Ying; Tse, Yee‐Kit; Hui, Vicki Wing‐Ki; Liang, Lilian Yan; Chan, Henry Lik‐Yuen; Hui, David Shu‐Cheong; Wong, Grace Lai‐Hung (Hepatology (Baltimore, Md.), 2021)
Background and Aims We compared risk of acute liver injury and mortality in patients with COVID‐19 and current, past, and no HBV infection. Approach and Results This was a territory‐wide retrospective cohort study in Hong Kong. Patients with COVID‐19 between January 23, 2020, and January 1, 2021, were identified. Patients with hepatitis C or no HBsAg results were excluded. The primary outcome was mortality. Acute liver injury was defined as alanine aminotransferase or aspartate aminotransferase ≥2 × upper limit of normal (ULN; i.e., 80 U/L), with total bilirubin ≥2 × ULN (i.e., 2.2 mg/dL) and/or international normalized ratio ≥1.7. Of 5,639 patients included, 353 (6.3%) and 359 (6.4%) had current and past HBV infection, respectively. Compared to patients without known HBV exposure, current HBV‐infected patients were older and more likely to have cirrhosis. Past HBV‐infected patients were the oldest, and more had diabetes and cardiovascular disease. At a median follow‐up of 14 (9‐20) days, 138 (2.4%) patients died; acute liver injury occurred in 58 (1.2%), 8 (2.3%), and 11 (3.1%) patients with no, current, and past HBV infection, respectively. Acute liver injury (adjusted HR [aHR], 2.45; 95% CI, 1.52‐3.96; P < 0.001), but not current (aHR, 1.29; 95% CI, 0.61‐2.70; P = 0.507) or past (aHR, 0.90; 95% CI, 0.56‐1.46; P = 0.681) HBV infection, was associated with mortality. Use of corticosteroid, antifungal, ribavirin, or lopinavir–ritonavir (adjusted OR [aOR], 2.55‐5.63), but not current (aOR, 1.93; 95% CI, 0.88‐4.24; P = 0.102) or past (aOR, 1.25; 95% CI, 0.62‐2.55; P = 0.533) HBV infection, was associated with acute liver injury. Conclusion Current or past HBV infections were not associated with more liver injury and mortality in COVID‐19.